Development of Korean Teaching Model for Surgical Procedures in Trauma -Essential Surgical Procedures in Trauma Course- - Hohyun Kim; Chan-Yong Park; Hyun-Min Cho; Kwang-Hee Yeo; Jae Hun Kim; Byungchul Yu; Seung-Je Go; Oh Sang Kwon (Journal of Trauma and Injury)
Purpose The Essential Surgical Procedures in Trauma (ESPIT) course was developed as a model to teach necessary surgical procedures to trauma physicians. Its goals are to improve knowledge, self-confidence, and technical competence. Methods The ESPIT course consisted of five lectures and a porcine lab operative experience. The ESPIT course has been run seven times between February 2014 and April 2016. ESPIT participants completed a questionnaire to assess self-efficacy regarding essential surgical procedures in trauma before and immediately after taking the ESPIT course. Sixty-three participants who completed both pre- and post-course questionnaires on self-efficacy were enrolled in this study. Results The overall post-ESPIT mean self-efficacy score was higher than the pre-ESPIT mean self-efficacy score (8.3±1.30 and 4.5±2.13, respectively) (p<0.001). Self-efficacy was significantly improved after the ESPIT course in general surgeons (p<0.001), thoracic and cardiovascular surgeons (p<0.001), emergency medicine doctors, and others (neurosurgeons, orthopedic surgeons) (p<0.001). The differences in self-efficacy score according to career stage (<1 year, 1–3 years, 3–5 years, and >5 years) were also statistically significant (p<0.001). Conclusions The data of the ESPIT participants indicated that they felt that the ESPIT course improved their self-efficacy with regard to essential surgical procedures in trauma. The ESPIT course may be an effective strategy for teaching surgical procedures, thus promoting better management of traumatic injuries.